Pengaruh Pemberian Kompres Hangat dan Aromaterapi Peppermint terhadap Nyeri Symphysis Pubis pada Ibu Hamil Trimester III - Wahyuni Wahyuni; Anis Ardiyanti; Nafisatun Nisa (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The third trimester of pregnancy is the final trimester of pregnancy, in this period the fetus grows within a period of 29-40 weeks, where this period is the time to prepare for childbirth. During the pregnancy process, physical and psychological changes will occur. Physical changes can cause discomfort such as pain in the symphysis pubis. Pubic symphysis pain occurs because during pregnancy there will be an increase in the height of the uterine fundus. Efforts to alleviate pubic symphysis pain include warm compresses and peppermint aromatherapy. This study aims to determine the effect of warm compresses and peppermint aromatherapy on pubic symphysis pain in third trimester pregnant women. This is a quantitative study with a quasi-experimental design using approach one group pretest-posttest design without control group. The total sample consisted of 66 third trimester pregnant women, selected using a purposive sampling technique. The Wilcoxon test results showed a significant effect of warm compresses and peppermint aromatherapy on reducing pubic symphysis pain, with a p-value of 0.000 (≤ 0.05). Warm compresses and peppermint aromatherapy can be used as nursing interventions to reduce pubic symphysis pain in third trimester pregnant women.